8-Cetylcoptisine, a new coptisine derivative, induces mitochondria-dependent apoptosis and G0/G1 cell cycle arrest in human A549 cells. (1st February 2019) - Han, Bing; Jiang, Pu; Xu, Heshan; Liu, Wuyang; Zhang, Jian; Wu, Siqi; Liu, Liangyu; Ma, Wenyu; Li, Xuegang; Ye, Xiaoli
Abstract: Lung cancer is the worldwide leading cause of cancer-related death. Here, we described the synthesis and the anticancer activity of a novel coptisine derivative 8-cetylcoptisine (CCOP) on lung carcinoma in vitro and in vivo . CCOP inhibited the cell viability of A549, BGC-823, MDA-MB-231, HCT-116 and HepG2 cell lines. In A549 cells, CCOP induced apoptosis, G0/G1 cell cycle arrest and decreased mitochondrial membrane potential (MMP) in a dose-dependent manner. Western blot analysis showed that CCOP increased the expression of Bcl-2-associated X protein (Bax), cleaved caspase 3 and 9, while decreased B-cell lymphoma 2 (Bcl-2), cyclins D and E, cyclin dependent kinases (CDKs) 2, 4 and 6, along with the inactivation of the upstream phosphoinositide 3-kinase (Pi3k)/protein kinase B (Akt) signaling. Further in vivo studies showed that CCOP (10 mg/kg) significantly delayed tumor growth in A549 xenograft nude mice, which is stronger than that of coptisine (100 mg/kg). These data suggested that CCOP could be a candidate for lung cancer therapy. Graphical abstract: Highlights: A new coptisine derivative 8-cetylcoptisine is synthesized and characterized. CCOP inhibits cell growth in A549 and other cancer cell lines. CCOP induces mitochondria-dependent apoptosis and G0/G1 arrest in A549 cells. CCOP exhibits better antitumor effect than COP in A549 xenograft nude mice.